A Study on the effect of iron folic acid supplementation and deworming among college going adolescent girls in urban Agra. - Lamba, Ratandeep; Misra, Sunil Kumar; Rana, Ravi (Indian Journal of Community Health, 2014)
Background: Spaced IFA Supplementation is recognized as an efficacious public health program and effective preventive approach in combating anemia in adolescent girls, is cost effective and results in fewer side effects. Aim: To study the effect of: bi-weekly supplementation of IFA with and without Albendazole administration on the status of hemoglobin level in college going adolescent girls. Material and methods: An interventional study was conducted among college going girls in Agra in the age group of 16-19 years (n=300) who were randomly selected. Their Hemoglobin levels were estimated before and after intervention by the Cynmeth-hemoglobin method using Drabkin’s solution. Three groups [two study A and B and one control] of hundred girls each were randomly constituted. To the study groups, supervised bi-weekly IFA with and without Albendazole were administered respectively for three months. Data collected was analyzed using suitable statistical tools. Results &Discussion: The overall prevalence of anemia was 65.3%.The initial prevalence in study group reduced significantly from 80.7% to 35.5% whereas in study group B it reduced from 73.5% to 58.8% and in control it remained almost same 84.3% and 81.2% pre and post intervention respectively. The mean Hemoglobin rise observed in the study group A and B was 2.5gm/dl and 2.3 gm/dl respectively while in control group fall in the mean Hb was observed (0.1gm/dl). Conclusion: The prevalence of anemia in adolescent girls is high. Supervised IFA therapy twice a week is an effective strategy to lower the prevalence of anemia either combined or uncombined with Albendazole.